Extending a Hand in Perilous Times: Beneficial Immigration Policy in the Fifty States, 2005–2012. (29th October 2020) - Sanchez, Lisa M.; Williams, Isabel
Abstract : Objective: The passage of Arizona SB 1070 in 2010 focused national attention on punitive, state‐level immigration legislation. Largely ignored is the increasing number of beneficial, state‐level policies passed during the same period. We seek to understand whether beneficial immigration policy making amounts to reversing the factors underlying punitive immigration policy making, as is implied by current literature. Methods: We utilize data from the National Conference of State Legislatures from 2005 to 2012 to uncover the puzzling enactment of beneficial state immigration laws during a period of high anti‐immigrant sentiment and budgetary declines in the 50 states. Results: Beneficial immigration policy making is not a reversal of the process that underlines punitive immigration policy making and is particularly responsive to the need generated by immigrant population size, regardless of the documentation status of the beneficiary. Conclusion: The passage of beneficial immigration policies requires further analysis, as it is not as simple as reversing the process that produces punitive immigration policies.